Effect of drip irrigation and NK fertigation on soil water dynamics and water productivity of strawberry under protected conditions - JASWAL, RICHA; SANDAL, SANJEEV K. (Journal of Soil and Water Conservation, 2023)
The present study was conducted during the year 2015-16 with the objectives to evaluate the effects of drip irrigation and NK fertigation levels on soil water retention and transmission, water use efficiency (WUE) and productivity of strawberry under protected condition. The treatments comprised of three drip irrigation levels (DI0.6, DI0.8 and DI1.0), three NK fertigation levels (NK50, NK75 and NK100) and control (100% RDF applied through conventional method with drip irrigation at 1.0 PE). The results indicated that DI1.0 and DI0.8 treatment had higher soil water stock, profile water recharge in comparison to DI0.6 while WUE was higher in DI0.6. In case of different NK fertigation treatment, NK100 and NK75 had higher WUE, and higher marketable yield as compared to NK50 treatment. The study concluded that fertigation application of 100% RDF at 0.6 PE level resulted in higher water use efficiency and saving irrigation water. However, the maximum marketable yield was obtained with DI0.8 NK100